2007
DOI: 10.1007/s10140-007-0686-x
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of acute bowel pathology: a pictorial review

Abstract: The purpose of this pictorial essay is to describe magnetic resonance (MR) imaging features of acute processes involving the bowel. While computed tomography (CT) is likely to remain the modality of choice in this setting, the advantages of MR include high soft tissue contrast, lack of ionizing radiation, and the ability to administer gadolinium in patients with a history of allergic reaction to iodinated contrast material. With the increasing utilization of abdominal/pelvic MR, radiologists must recognize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…Magnetic resonance imaging (MRI) represents a non-invasive imaging modality without the need of radiation exposure, also for the evaluation of the gastrointestinal tract, including diverticular disease (14). With regard to the diagnostic of inflammatory diseases of the gastrointestinal tract, previous research showed that MRI is a feasible alternative modality to computed tomography (CT) in the diagnosis and evaluation of acute colonic diverticulitis with high sensitivity and specificity (14)(15)(16)(17)(18). However, there are no studies analyzing the presence and extent of asymptomatic diverticulosis by MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) represents a non-invasive imaging modality without the need of radiation exposure, also for the evaluation of the gastrointestinal tract, including diverticular disease (14). With regard to the diagnostic of inflammatory diseases of the gastrointestinal tract, previous research showed that MRI is a feasible alternative modality to computed tomography (CT) in the diagnosis and evaluation of acute colonic diverticulitis with high sensitivity and specificity (14)(15)(16)(17)(18). However, there are no studies analyzing the presence and extent of asymptomatic diverticulosis by MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover the computed tomography colonography (CTC) seems to be a reasonable alternative in follow-up of patients with symptomatic diverticular disease [45]. In recent years, magnetic resonance imaging (MRI) has gained popularity, because it lacks the ionizing radiation and even if CT remains the modality of choice; however MRI can similarly demonstrate findings of diverticulitis and could be useful in diagnosis of ischemic colitis [46,47]. Although, colonic diverticulitis is easily diagnosed and classified (graded) by CT than by ultrasound (US), it is important to be aware of the US signs of diverticulitis considering that US is often used as a first modality in the diagnostic approach to the acute abdomen.…”
Section: Main Bodymentioning
confidence: 99%
“…Computed tomography (CT) and ultrasonography (US) are the most commonly used imaging modalities in patients with acute abdomen. Magnetic resonance imaging (MRI), on the contrary, is less frequently employed in these patients because of its limited availability, high costs and motion artefacts, which have prevented its use in the diagnostic workup of acute intestinal diseases for several years [11]. The latest MRI devices, however, have faster image acquisition speed and greater contrast resolution for soft tissues and have become more widely available [12].…”
Section: Introductionmentioning
confidence: 98%
“…La tomografi a computerizzata (TC) e l'ultrasonografi a (US) sono le metodiche di imaging più comunemente impiegate nell'approccio al paziente con addome acuto. La risonanza magnetica (RM), al contrario, è meno utilizzata nella gestione del paziente con patologia addominale acuta, per la sua limitata disponibilità, per i costi elevati e per artefatti da movimento che ne hanno precluso per anni l'impiego nell'iter diagnostico della patologia intestinale acuta [11]. Le più recenti apparecchiature di RM presentano incrementata velocità di acquisizione delle immagini, un'aumentata capacità di contrasto per i tessuti molli e maggiore diffusione sul territorio [12].…”
unclassified